2020
DOI: 10.3390/ijms21155458
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-Dependent Targeting of RSU1 and the IPP Adhesion Complex Regulates the PTEN/PI3K/AKT Signaling Pathway in Breast Cancer Cell Lines

Abstract: (1) Background: The microRNA (miR)-directed control of gene expression is correlated with numerous physiological processes as well as the pathological features of tumors. The focus of this study is on the role of miRs in the regulation of RSU1 and proteins in the IPP (integrin linked kinase, PINCH and parvin) complex. Because the IPP adaptor proteins link β integrins to actin cytoskeleton, and the RSU1 signaling protein connects the complex to the activation of cJun, ATF2 and the transcription of PTEN, their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…Our study also con rmed the connection between signals in recipient cells and mediators within exosomes. Previous studies have demonstrated that the effects of miR-221-3p were mediated via increasing Akt kinase activity and inhibiting PTEN [59,60]. In agreement with these ndings, our results showed that the inhibitors of miR-221-3p attenuated enhanced expression of PTEN and p-Akt induced by hucMSC-Exos.…”
Section: Discussionsupporting
confidence: 92%
“…Our study also con rmed the connection between signals in recipient cells and mediators within exosomes. Previous studies have demonstrated that the effects of miR-221-3p were mediated via increasing Akt kinase activity and inhibiting PTEN [59,60]. In agreement with these ndings, our results showed that the inhibitors of miR-221-3p attenuated enhanced expression of PTEN and p-Akt induced by hucMSC-Exos.…”
Section: Discussionsupporting
confidence: 92%
“…In order to evaluate the expression of several miRNAs that have been reported as related to BCa development and progression [ 11 , 12 , 13 , 14 , 15 ], we developed a triple negative BCa (TNBC) mice model. Balb/c animals were randomly divided into two groups (BCa or control) and inoculated or not with 4T1 cells.…”
Section: Resultsmentioning
confidence: 99%